(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Cannabis use has emerged as a major public health and educational concern in Nigeria, particularly within Delta State, where socio-economic instability and youth vulnerability intersect. This study investigated the socio-economic factors influencing cannabis use among citizens of Delta State and examined the implications for drugs education. Guided by Strain Theory and Social Learning Theory, the research adopted a descriptive survey design. A sample of 400 participants, drawn using multistage sampling techniques, provided data through structured questionnaires. Data were analyzed using descriptive statistics, chi-square tests, and regression analysis. Findings revealed that poverty, unemployment, peer influence, cultural tolerance, and availability were the strongest predictors of cannabis use. Peer influence was particularly significant, indicating the role of social networks in sustaining substance use. Results further demonstrated that cannabis use adversely affects academic performance, cognitive development, and health outcomes, highlighting critical challenges for educational systems and public health in Delta State. The study concluded that cannabis use is not merely a matter of individual choice but is deeply embedded in socio-economic realities. Accordingly, drug education in Delta State should be contextualized, integrating socio-economic empowerment, peer-based interventions, and cultural engagement strategies. The study recommends a multi-sectoral approach involving government, schools, communities, and health institutions to design effective prevention and rehabilitation programs. Future research should examine gender-specific patterns of cannabis use and evaluate the effectiveness of current drug education interventions in Nigeria.